2016
DOI: 10.1039/c5md00439j
|View full text |Cite
|
Sign up to set email alerts
|

Novel indole–flutimide heterocycles with activity against influenza PA endonuclease and hepatitis C virus

Abstract: Structure-based design and synthesis of novel indole–flutimide derivatives with antiviral activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…Rice, The Rockefeller University, NY) 27 of HCV 3a (strain S52) and 4a (strain ED43), respectively. 28…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Rice, The Rockefeller University, NY) 27 of HCV 3a (strain S52) and 4a (strain ED43), respectively. 28…”
Section: Experimental Sectionmentioning
confidence: 99%
“…It is noteworthy that the activity of 18 (EC 50 = 0.25 μM) was 12-fold better than lead compound 16 (EC 50 = 2.92 μM). A marked improvement was also observed on the EC 50 value of 16 (43-fold lower), compared to the structurally related fused indole-flutimide analogue I (EC 50 = 126.3 μM), 56 validating the idea of incorporating a spiro connection between hydantoin and the indane ring. Introduction of a methyl substituent on the amide nitrogen atom of the 2,4diketoimidazolidine scaffold of 16 led to a 2-fold increase in the activity (EC 50 16a = 1.41 μM).…”
Section: Biologymentioning
confidence: 53%
“…Rational designtheoretical calculations Previous studies by our group have resulted in compounds carrying metal chelating moieties that demonstrated a highly promising inhibition capacity against either pathogenic viruses, including influenza and HCV, 56 or parasites of the Trypanosoma genus. 57,58 The two above-mentioned series of analogues, although structurally diverse, were based on rational incorporation of metal chelating moieties on scaffolds with pronounced drug-likeness, such as the combination of flutimide with the indole system (I) or incorporation of the acetohydroxamic acid moiety on a 2,6-diketopiperazine (2,6-DKP) scaffold (II) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds #1, 41–45, 78–91, 138–140, and 190 were reported previously (Cai et al, 2014). Compounds #236–241 were synthesized as previously reported (Zoidis et al, 2016). Compounds #128, 132, 191, 197, 198, 204, 206, 208, 211, and 217 were purchased commercially.…”
Section: Methodsmentioning
confidence: 99%